Survival and biofilm formation of Listeria monocytogenes in simulated vaginal fluid: influence of pH and strain origin - Borges, Sandra F. (2012)
Listeria monocytogenes, the agent responsible for listeriosis, can be transmitted from mother to fetus/neonates by vertical transmission, transplacentally or during passage through the birth canal. The purpose of this study was to investigate the survival and biofilm formation of L. monocytogenes (isolated from clinical cases or from food) in simulated vaginal fluid at different pH values (4.2, 5.5 and 6.5). The results demonstrated that this pathogen is inhibited by the normal vaginal pH, but may proliferate when it increases. Clinical strains were significantly more resistant to pH 4.2 than food isolates. Listeria monocytogenes survived and even grew at the higher pHs investigated, suggesting that fetus/neonates from women having increased vaginal pH values during pregnancy may be at a higher risk of listeriosis. All isolates tested were producers of biofilm at different pH values; however, L. monocytogenes produced higher quantities of biofilm in a nutrient-rich medium. No significant differences in biofilm production were detected between food and clinical isolates. As L. monocytogenes are biofilm producers, this increases the probability of occurrence of neonatal infection.